DIODE LASER TREATMENT OF ORTHODONTICALLY INDUCED GINGIVAL HYPERPLASIA. A RANDOMIZED CONTROLLED CLINICAL TRIAL - Aboelsaad, Nayer; Attia, Nahed (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿Gingival hyperplasia becomes a relatively frequent pathologic condition during orthodontic treatment. The aim of this study was to evaluate the effectiveness of diode laser gingivectomy as an adjunct to nonsurgical periodontal treatment in the management of gingival hyperplasia in orthodontic patients. Materials and Methods: Thirty eight orthodontic patients with gingival enlargement due to fixed appliances were divided randomly into two groups. The test group received diode laser (810-nm) gingivectomy as an adjunct to nonsurgical periodontal treatment. The control group received nonsurgical periodontal treatment only. For all patients, clinical periodontal parameters were assessed at baseline, 6weeks, and 12 weeks: Plaque Index, Gingival Index, bleeding on probing, probing pocket depth, and Gingival Overgrowth Index. Intra- and intergroup variations in the periodontal parameters were determined at time intervals versus baseline measurements. Results: Both groups showed statistically significant improvements in clinical periodontal parameters over the study period (P < .05). However, significant improvements in periodontal health were evident earlier in the test group as the extent of improvement in periodontal health compared to baseline was greater in the test group than in the control group for most of the clinical parameters. (P< .05) Conclusion: The adjunct use of diode laser gingivectomy combined with meticulous oral hygiene can produce quicker and greater improvement in gingival health, suggesting its beneficial use for orthodontic patients with gingival overgrowth